THE USE OF FANTASY AND NONSENSE IN CARROLL’S WRITING (Лучшие интеллектуальные исследования, 2025)
This article explores the prominent role of fantasy and nonsense in Lewis Carroll’s literary works, examining how these elements serve to challenge conventional notions of logic, reality, and language. Through an analysis of Carroll’s use of whimsical characters, imaginative worlds, and playful linguistic constructions, the study highlights how his writing invites readers into a surreal universe that blurs the boundaries between fiction and reality. The article also considers the cultural and psychological implications of nonsense as a means of fostering creativity, critical thinking, and childlike wonder. Ultimately, the paper illustrates how Carroll’s masterful integration of fantasy and nonsense not only defines his unique literary style but also engages readers in a deeper questioning of the nature of perception and understanding.